PENGARUH PENDIDIKAN PEMILIK, MASA MEMIMPIN, UMUR PERUSAHAAN, PELATIHAN AKUNTANSI, DAN EKSPEKTASI KINERJA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA UKM DI KABUPATEN MALANG - Ramadhani, Febrinda Rizky; Lestari, Puji; Supeno, Saras (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2018)
This research aims to analyze and describe the factors that affect the use of accounting information in small and medium enterprises. Factors that used to affect the use of accounting information in this study are the owner educational background, lead time, bussiness age, accounting training, and performance expectancy.   The population in this study was all of the potential SMEs in Kabupaten Malang. This research used proportionate stratified random sampling technique by determining sample to small group and medium group. Samples obtained in this research were 86 respondents. Data collection techniques with survey techniques with questionnaires distribution and data analysis techniques in this study using multiple regression analysis techniques with the help of SPSS software. The results of this research conclude that the application accounting information of SMEs is influenced by the owner educational background, the length of time owner managing, bussiness age, accounting training, and performance expectancy. Keywords: owner educational background, lead time, bussiness age, accounting training, performance expectancy, the use of information accounting.